Factors of social networking towards the development of self-esteem, social skills and learning behavior among adolescents - Balan Rathakrishnan; Mohammad Amin Wani; Sajad Ahmad Bhat; Azizi Yahaya; Soon Singh Bikar Singh; Mohammad Rahim Kamaluddin; Manish Kumar Verma (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The fundamental object of the current research was to identify the factors of social networking sites in the development of self-esteem, social skills & learning behavior among adolescents in Malaysia, for this purpose sample of 220 students were randomly selected from different seven schools in Johor Bahru town of Malaysia. The obtained primary data was statistically analyzed by descriptive statistics through SPSS 20 version. Results demonstrated that Instant messenger is the most prevailing factor in contributing the self esteem, social skill & learning behaviour. Further it is also unveiled that social network sites viz Facebook, Twitter and YouTube have their influence on adolescent development. The research also gives the detailed descriptive discussion about how the social networking contributes towards the development of selected variables.